2008
DOI: 10.2174/1875397300801010002
|View full text |Cite
|
Sign up to set email alerts
|

The Use of AlphaScreen Technology in HTS: Current Status

Abstract: AlphaScreen (Amplified Luminescent Proximity Homogeneous Assay Screen) is versatile assay technology developed to measuring analytes using a homogenous protocol. This technology is an example of a bead-based proximity assay and was developed from a diagnostic assay technology known as LOCI (Luminescent Oxygen Channeling Assay). Here, singlet oxygen molecules, generated by high energy irradiation of Donor beads, travel over a constrained distance (approx. 200 nm) to Acceptor beads. This results in excitation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
190
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(192 citation statements)
references
References 39 publications
1
190
0
1
Order By: Relevance
“…The bicycle and HECT were immobilized on streptavidin and anti-GST IgG coated donor and acceptor beads, respectively. In the Alpha assay, an optical signal is obtained when donor and acceptor are linked by ligands, and compounds that disrupt the binding result in a decreased signal (15). A counter screen using biotinylated GST to link the beads was used to eliminate compounds that interfere nonspecifically with the optical readout.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The bicycle and HECT were immobilized on streptavidin and anti-GST IgG coated donor and acceptor beads, respectively. In the Alpha assay, an optical signal is obtained when donor and acceptor are linked by ligands, and compounds that disrupt the binding result in a decreased signal (15). A counter screen using biotinylated GST to link the beads was used to eliminate compounds that interfere nonspecifically with the optical readout.…”
Section: Significancementioning
confidence: 99%
“…We found that these frequently targeted the E2 binding site and inhibited ligase activity in vitro. We then used Alpha screening technology (15) to identify molecules that disrupted the bicycle-Smurf2 interaction. We identified one compound, termed heclin (HECT ligase inhibitor), that inhibits a range of HECT ligases in vitro and in tissue culture cells, with IC 50 s in the low micromolar range.…”
mentioning
confidence: 99%
“…1). When used in a homogenous AlphaLISA assay (Eglen et al 2008), this pair of antibodies detected a standard of Fc-EDA1 diluted in EDA-deficient serum with a sensitivity of about 0.1 ng/ml in as little as 2.5 µl of serum. Signals obtained in a panel of XLHED sera were consistently very low (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This light is quenched by a nearby Europium chelate that emits the final signal at 615 nm (Eglen et al 2008). This system is particularly suited for measures in sera, even hemolysed, because absorption spectra of hemoglobin and other serum proteins are low above 600 nm.…”
Section: Titles and Legends To Figuresmentioning
confidence: 99%
“…Alternative signal generation methods have been developed, such as electrochemiluminescence detection (Meso Scale Discovery), which provides a much greater dynamic range and sensitivity compared to HRP based signals (Zhao et al 2004). Fluorescent bead-based technologies, such as those developed by Luminex and PerkinElmer's AlphaScreen® are also alternatives to standard solid phase ELISAs (Kellar et al 2006;Eglen et al 2008). These are analogous to ELISA sandwich assays, but use suspended beads as the solid phase in the assay, rather than the plate surface.…”
Section: Introductionmentioning
confidence: 99%